Extranodal NK/T-cell lymphoma of nasal type with midline symmetry oral ulcer as the main symptom: A case report and literature review - YU Donglin; CAO Zhang; WANG Wenlong; MA Xiangrui; TANG Juan; ZUO Jinhua (Kouqiang hemian waike zazhi)
[Objective:] To investigate the clinicopathological features, diagnosis and treatment of extranodal NK/T-cell lymphoma of nasal type (ENKTL-NT), and to provide reference for the diagnosis and treatment of clinicians. [Methods:] A case of palatal mucosa with a midline symmetry ulcer was followed up and ENKTL-NT was discussed, and analyzed in combination with literature. [Results:] After multiple biopsies were taken and the diagnosis was confirmed, the patient's condition was obviously improved by combined treatment. During nine months of postoperative follow-up, the patient died. [Conclusion:] ENKTL-NT is rare for stomatologists, and its clinical features are complex. Biopsy is often difficult to confirm the diagnosis. It is necessary to implement repeated multi-site biopsy strategies to improve diagnostic accuracy.